Uganda : First Review Under The Policy Support Instrument. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses Uganda's First Review Under the Policy Support Instrument (PSI). Growth has continued to recover from the 2011-2012 low. In an environment of declining inflation-recently halted by a drought-driven food price shock-the fiscal stimulus has been successful in driving economic activity, and a planned program of infrastructure investment is expected to boost growth further. The external accounts remain sustainable. The current account deficit declined mainly owing to a temporary slowdown of foreign direct investment-related imports. With satisfactory program performance, IMF staff supports completing the first PSI review and increasing the ceiling on nonconcessional borrowing.